HUBUNGAN SIKAP KERJA ERGONOMI TERHADAP KELELAHAN OTOT TANGAN PADA TINDAKAN RESTORASI RESIN KOMPOSIT GIGI ANTERIOR OLEH MAHASISWA PROFESI KEDOKTERAN GIGI - Putu Lestari Sudirman; Desak Nyoman Ari Susanti; Sari Kusumadewi; Ni Wayan Ditami (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Dentist profession is a profession prone to musculoskeletal disorders (MSDs) due to the demands of working in a limited area and requiring high concentration. One of the treatments requiring high concentration is composite resin restoration on anterior teeth since it is closely related to esthetic functional recovery. The high demand for work results in dentists not being aware of working ergonomically, leading to fatigue which can increase the risk of MSDs. The study aimed to discover the relationship between ergonomic working and hand muscle fatigue on the anterior dental composite resin restoration by professional students of the Bachelor of Dentistry and Professional Dentistry Study Program (PSSKGPDG) Faculty of Medicine, Udayana University. The study was conducted using the cross-sectional analytic method by measuring hand muscle fatigue before and after treatment using a hand dynamometer. The working attitude was observed via pictures taken using a digital camera, then analyzed using the RULA method for 29 samples. The differential data of hand muscle fatigue before and after treatment was correlated with the RULA score with the rank spearman method presented in a table. The study result showed that the working attitude in the mild risk occurred in three people (10.3%), 26 people (89.7%) in the moderate risk, and 0% in the non-risky and high-risk categories. Hand muscle fatigue occurred marked by decreased hand muscle strength of 3.38 kg on average. Before the treatment, hand muscle strength was 25.31 kg and reduced to 21.93 kg after the treatment. Hand muscle strength of respondents was categorized as very poor before and after the treatment. The study acquired p value = 0.001 and r = 0.650, indicating a strong relationship between ergonomic working attitude and hand muscle fatigue on the anterior dental composite resin treatment by professional students of PSSKGPDG Faculty of Medicine, Udayana University.